Distance Learning in Higher Education: Evidence from a Randomized Experiment - M. Paula Cacault; Christian Hildebrand; Jérémy Laurent-Lucchetti; Michele Pellizzari (Institute of Labor Economics (IZA), 2019)
Using a randomized experiment in a public Swiss university, we study the impact of online live streaming of lectures on student achievement and attendance. We find that (i) students use the live streaming technology only punctually, apparently when random events make attending in class too costly; (ii) attending lectures via live streaming lowers achievement for low-ability students and increases achievement for high-ability ones and (iii) offering live streaming reduces in-class attendance only mildly. These findings have important implications for the design of education policies.
Keywords: I20; I21; I23; I26; 330; EduTech; distance learning; live streaming